Assessment of potential public health impact of a quadrivalent inactivated influenza vaccine in Thailand. Issue 3 (29th January 2016) - Kittikraisak, Wanitchaya; Chittaganpitch, Malinee; Gregory, Christopher J.; Laosiritaworn, Yongjua; Thantithaveewat, Thanawadee; Dawood, Fatimah S.; Lindblade, Kim A.
Abstract : Background: Each year, an influenza B strain representing only one influenza B lineage is included in the trivalent inactivated influenza vaccine (IIV3); a mismatch between the selected lineage and circulating viruses can result in suboptimal vaccine effectiveness. We modeled the added potential public health impact of a quadrivalent inactivated influenza vaccine (IIV4) that includes strains from both influenza B lineages compared to IIV3 on influenza‐associated morbidity and mortality in Thailand. Methods: Using data on the incidence of influenza‐associated hospitalizations and deaths, vaccine effectiveness, and vaccine coverage from the 2007–2012 influenza seasons in Thailand, we estimated rates of influenza‐associated outcomes that might be averted using IIV4 instead of IIV3. We then applied these rates to national population estimates to calculate averted illnesses, hospitalizations, and deaths for each season. We assumed that the influenza B lineage included in IIV3 would provide a relative vaccine effectiveness of 75% against the other B lineage. Results: Compared to use of IIV3, use of IIV4 might have led to an additional reduction ranging from 0·4 to 14·3 influenza‐associated illnesses per 100 000 population/year, <0·1 to 0·5 hospitalizations per 100 000/year, and <0·1 to 0·4 deaths per 1000/year. Based on extrapolation to national population estimates, replacement of IIV3 with IIV4 might have averted an additional 267–9784 influenza‐associated illnesses, 9–320 hospitalizations, and 0–3 deaths. Conclusion: Compared to use of IIV3, IIV4 has the potential to further reduce the burden of influenza‐associated morbidity and mortality in Thailand.